Use of ocean plastic waste for 3D printing filament - Khaw, Ian Kuang Li (Nanyang Technological University, 2021)
The use of plastics has permeated through every single part of our lives, from the packaging of the food we consume and the electronics in our hands. Plastics are currently being consumed more and more, which has led to the undesired consequence of having to dispose of these plastics. Unwittingly, many of these plastic wastes end up in our oceans and seas, leading to many environmental problems. In order to promote the removal of plastic waste from the ocean, an alternative use to the waste plastic collected can be considered. This report aims to create a filament that can be used for 3D printing using waste polypropylene (PP) and waste polyethylene (PE) collected. The waste plastics will first be cut down and cleaned, before being pelletized into pellets. The pelletized waste plastic can then be processed using a filament maker to create a filament that is suitable for use in a 3D printer. The characterisation as well as the operating temperatures that are suitable for the processing of the recycled PEPP (rPEPP) blend were determined through testing the characteristics and thermal properties of the rPEPP blend, ensuring that the blend does not degrade during processing.